Whole cottonseed, vitamin E and finishing period affect the fatty acid profile and sensory traits of meat products from Nellore cattle - Ferrinho, Adrielle M.; Nassu, Renata T.; Aldai, Noelia; Bravo-Lamas, Leire; Furlan, Maisa L. N.; Toda, Beatriz M.; Utembergue, Bruno L.; Rezende, Romulo G.; Mueller, Lenise F.; Furlan, Joyce J. M.; Zanata, Mariana; Baldi, Fernando [UNESP]; et al. (Elsevier B.V., 2018)
This study investigated how different finishing periods and the inclusion of whole cottonseed and vitamin E in diets fed to feedlot cattle affect meat lipid composition and sensory traits of fresh beef and hamburgers. Fifty-four Nellore bulls were fed 3 different diets (C: control; WCS: 30% whole cottonseed; WCSE: 30% whole cottonseed plus vitamin E) during finishing periods of 83, 104, and 111 days. The inclusion of cottonseed did not affect saturated fatty acid levels (SFA), but increased the levels of certain polyunsaturated fatty acids (PUFA) in meat. The SFA levels and n-6/n-3 ratio increased over the length of finishing period. In general, meat products from animals fed the WCS and WCSE diets were more tender and juicier (P < 0.05); however, an off-flavor was detected by the panelists (P < 0.05). The sensory difference test results showed that the WCS hamburger flavor was not significantly different for the studied lengths of finishing period. Addition of 30% DM cottonseed in diets for cattle did not promote changes likely to affect human health, and it provided a more tender and juiciness meat, however differences in the off flavor were perceived only by panelist.
Keywords: Antioxidant; Lipid composition; Hamburger; Oilseed; Descriptive test; Off-flavor